Vitamin D and Its Relationship with Markers of Bone Metabolism in Healthy Asian Women. Issue 4 (12th July 2013) - Tan, Karen M.L.; Saw, Sharon; Sethi, Sunil K.
<x xml:space="preserve">Abstract</x> Background In this study, we aimed to determine the normal ranges of 25‐hydroxy‐vitamin D3 (25‐OHD3), parathyroid hormone (PTH), and the markers of bone turnover, procollagen type 1 N propeptide (P1NP) and C‐terminal cross‐linked telopeptide of type 1 collagen (CTX), in normal healthy women in Singapore, and to explore the relationship between vitamin D, PTH, and these markers of bone turnover in the women. Methods One hundred and ninety‐seven healthy women, aged 25 to 60, were selected from a hospital staff health screening program; 68% were Chinese, 18% Malay, and 14% Indian. P1NP, CTX, and 25‐OHD3 were measured using the Roche Cobas® electrochemiluminescence immunoassay. Serum PTH was measured using the Siemens ADVIA Centaur® immunoassay. Results Sixty‐five percent had 25‐OHD3 concentrations <50 nmol/l. Vitamin D insufficiency (25‐OHD3 < 50 nmol/l) was more prevalent in Malays (89%) and Indians (82%) compared to Chinese (56%). There was no correlation between vitamin D and age. PTH positively correlated with age, and Malays and Indians had higher PTH concentrations than Chinese. There was an inverse correlation between PTH and 25‐OHD3, but no threshold of 25‐OHD3 concentrations at which PTH plateaued. The bone turnover markers P1NP and CTX inversely correlated with age but were not different between ethnic groups. CTX and P1NP exhibited good correlation, however, there was no significant correlation between 25‐OHD3 or PTH concentrations and the bone turnover markers P1NP and CTX. Conclusions Healthy women in Singapore have a high prevalence of vitamin D insufficiency. Vitamin D insufficiency was more prevalent in Malays and Indians compared to Chinese.